Enhanced post crown retention in resin composite-reinforced, compromised, root-filled teeth: a case report - Lui, J.L. (1999)
The introduction of an intraradicular composite reinforcing technique, in conjunction with the reestablishment of matching post canal spaces, has allowed compromised, root-filled teeth to be restored with functional, esthetic post crowns. This clinical case report suggests that reconstituted post canals, in accurately adapting to passive, parallel-sided, matching, and well-fitting posts, can enhance the retention of post crowns. Other factors of clinical importance relating to the resin-reinforced technique are discussed, including fracture resistance, depth of polymerization, dentin adhesion, polymerization shrinkage, and coronal microleakage.